2020
DOI: 10.1093/icesjms/fsaa104
|View full text |Cite
|
Sign up to set email alerts
|

Regional and stock-specific differences in contemporary growth of Baltic cod revealed through tag-recapture data

Abstract: The use of growth estimation methods that depend on unreliable age data has previously hindered the quantification of perceived differences in growth rates between the two cod stocks inhabiting the Baltic Sea. Data from cod tagged in different regions of the Baltic Sea during 2007–2019 were combined, and general linear models were fit to investigate inter-regional (defined as area of release) and inter-stock (assigned to a subset of recaptures using genetic and otolith shape analyses) differences in individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…The results are in accordance with our previous studies using the RT-qPCR method and transcriptome sequencing [13,14,32]. All individuals used in this study have also been measured in length and weight and showed statistically significant differences between the WBC and EBC subpopulations (Figure 3), which is consistent with previous studies [54]. These results showed a poor condition of the EBC, which may cause difficulties in recovery of the stock [55].…”
Section: Discussionsupporting
confidence: 92%
“…The results are in accordance with our previous studies using the RT-qPCR method and transcriptome sequencing [13,14,32]. All individuals used in this study have also been measured in length and weight and showed statistically significant differences between the WBC and EBC subpopulations (Figure 3), which is consistent with previous studies [54]. These results showed a poor condition of the EBC, which may cause difficulties in recovery of the stock [55].…”
Section: Discussionsupporting
confidence: 92%
“…Among the elements regulated by physiological processes, P varies consistently over the seasons in both validation samples with minima co-occurring with otolith zones without visible daily increments in DECODE otoliths or, in the case of the TABACOD otoliths, in late winter/early spring. The amplitude in P is considerably larger in western compared to eastern Baltic cod corresponding to known stock-specific differences in growth rate (Bagge et al, 1994;McQueen et al, 2020) and experienced temperature amplitude, apparently with a smaller variation around the mean values in the western Baltic cod. Throughout the Baltic Sea, phosphate concentrations are low from April to September, presumably owing to a combination of increased primary production (Wulff and Rahm, 1988) coupled with a precipitation-related increase in P loading during fall/winter (Rolff et al, 2008) and recycling in the sediments in hypoxic areas ( ViktorssonPage 18 of 57 Canadian Journal of Fisheries and Aquatic Sciences (Author's Accepted Manuscript) et al, 2013).…”
Section: Seasonality In Element Patternsmentioning
confidence: 96%
“…The cod stocks also differ in several other parameters, e.g. the WBC stock has a lower stock size [ 11 ] but cod in the western Baltic Sea have a higher growth rate and reach larger sizes [ 12 , 13 ], their livers are less infested with anisakid larvae [ 14 ] and they have more easily readable otoliths [ 15 ].…”
Section: Introductionmentioning
confidence: 99%